Lymph Node Metastasis after a Soft Tissue Sarcoma of the Leg: A Case Report and a Review of the Literature - S. D. Nelen; F. J. Vogelaar; F. Gilissen; J. C. Van der Linden; K. Bosscha (Case Reports in Surgery)
Introduction. Soft tissue sarcomas (STSs) represent 1 percent of all adult malignancies and sarcomas only rarely spread to the regional lymph nodes. Case Presentation. We present a case of a woman with a dermatofibrosarcoma protuberans and a sarcoma not therwise specified of the lower extremity. The patient had no distant metastasis during follow-up, but did develop a regional lymph nodemetastasis (RLNM) in the groin. We reviewed the literature about RLNM in STSs. Discussion. Reviewing the literature we see that within specific histological types RLNM occurs as often as distant metastasis. Furthermore RLNM occurs in over 10% for specific histological types and in 24% of all patients with a soft tissue sarcoma of the lower extremity. Except for radical lymphadenectomy with a 5-year survival rate of 46% there is no appropriate treatment. Conclusion. The risk for a RLNM in certain histological types and anatomical locations might transcend the risk for a distant lung metastasis.